Jornalistas e redes sociais: o trabalho dos profissionais que atuam em agências de comunicação e sua relação com as prescrições sobre o Facebook - Lima, Tatiana Mara de Miranda (2022)
Social networks are among the most used digital platforms in the world. Brazil, in particular, occupies the first positions in the rankings of use of these platforms for personal and professional purposes. Communication workers, especially journalists that work in communication agencies, are some of the professionals who are working in activities straight related to social networks. After the decline of traditional media, such as magazines, newspapers, radios, and TVs, they have left the newsrooms and today they produce, in large part, contents to digital places, as social networks. This led to a several changes in work routines, starting with the need for a flexible and multiplatform performance, among other characteristics. Another demand to these professionals is constant updating, since the criteria used by social networks and their algorithms change frequently. Within this context, the guidelines and prescriptions presented by the social networks and also by the só-called experts in digital marketing are relevant. Thus, this research discussed the following problem question: how do the prescriptions of social networks and digital marketing specialists influence and guide the labor of journalists who work in communication agencies? For this, we studied these prescriptions, the work context of these professionals and possible consequences. As the object of this research, we chose the Facebook platform, belonging to the company Meta Platforms. This platform was chosen because it is the largest social network in the world, being used by most journalists who work in communication agencies. In addition, most of Facebook’s prescriptions are applicable to other social networks belonging to Meta Platforms, which makes this analysis more extensive. The research corpus consists of two types of documents: (1) Terms and policies of uses presented by Meta Platforms, (2) Contents published by digital marketing specialists, represented here by the company Rock Content. The material was analyzed with the support of knowledge from French tradition of Discourse Analysis, taking into account the sócio-political and ideological context of the production of the narratives. The main objective of this research was to understand how the prescriptions disseminated by Facebook and Rock Content relate to changes in the work of journalists who work in communication agencies. The assumption considered was that, more than simply transmitting content on social networks, the labor of journalists who work in communication agencies becomes dependent on these platforms. In addition, as it is immersed in a context of flexible accumulation, the labor of these professionals begins to contain characteristics inherent to a platform work. With this investigation, it was possible to broaden the understanding of the labor developed by journalists who work in communication agencies, especially with regard to the logic of platformization undertaken by social networks.